Optimización del actual sistema de inyección de agua a nivel de superficie en el campo C en la cuenca de Caguán-Putumayo mediante un análisis nodal (2020)
Waterflooding into oil reservoirs is the most widely used secondary recovery method that seeks to maintain the pressure of a reservoir. Field C is a mature field which has suffered a drop in the pressure of its reservoir, therefore a water injection system was developed to mitigate this problem. The water injection network was installed in 2013 and today it presents problems of pressure losses that are associated with the deposition of inorganic material (scale). These pressure losses lead to a decrease in the volume of water injected per day into the reservoir. In order to solve this complication, the behavior of the current injection system was simulated and the main restrictions to the natural flow of the injection water were identified through a nodal analysis to the system.